Analysis Of Students' Digital Literacy In Understanding Indonesian Explanatory Texts Through The Tiktok Education Platform - Hamzah, Muh Zuhdy; Aisyah, A. (UNIVERSITAS PAKUAN, 2025)
The development of digital technology, especially social media such as TikTok, has brought significant changes to the learning process in the modern era. However, there are still challenges related to students' digital literacy in utilizing these platforms effectively, especially in understanding complex and often considered difficult Indonesian explanatory text material. This study aims to analyze the extent to which students' digital literacy affects their understanding of explanatory texts through the use of TikTok Education. The research method used is qualitative with a case study approach, involving in-depth interviews with eight grade XI students and observations of the TikTok-based learning process. The results of the study show that TikTok provides a more interesting and contextual learning approach through short videos that combine animation and simple narration, thus helping students understand the concept of explanatory text structure such as general statements, explanatory sequences, and interpretations more effectively. In addition, student involvement in creating educational content improves digital literacy skills holistically, from searching for credible sources of information to producing logical and communicative narratives. However, weaknesses were found in the aspect of students' critical evaluation of the validity of information, where many students still rely on the popularity of content as a measure of truth. Therefore, the role of teachers as facilitators and content curators is very important to guide students in using TikTok wisely. In conclusion, TikTok has great potential as a medium for learning Indonesian, especially in understanding explanatory texts, if accompanied by comprehensive digital literacy development and appropriate teacher guidance. This study recommends the integration of adaptive, interactive, and sustainable digital learning strategies into the school curriculum.